Find the solutions
x=-2
x=6
(x-6)(x+2) =0
2007-02-01 03:10:38
·
answer #1
·
answered by catarthur 6
·
0⤊
0⤋
As usual all responders are correct, but I reckon you want to know how do this on your own. You're looking for a number that multiplies out to -12 and adds up to -4. This will have to be negative, as otherwise you couldn't end up with a negative number. At the same time the other root has to be positive, for the same reason. The only numbers that work here are -6 and 2. As you have a quadratic equation, there are two possible values for x: 6 or -2. Check it out in the original equation. Both work.
2007-02-01 11:26:23
·
answer #2
·
answered by obelix 6
·
0⤊
0⤋
(x - 6)(x + 2) = 0
so x - 6 = 0 or x + 2 = 0
gives x = 6 or x = -2
2007-02-01 11:11:47
·
answer #3
·
answered by Ken M 3
·
0⤊
0⤋
Given expression
=x^2-6x+2x-12
=x(x-6)+2(x-6)
=(x-6)(x+2)
As (x-6)(x+2)=0
Therefore either x-6=0 or x+2=0
Hence x=6 or -2
2007-02-01 11:19:25
·
answer #4
·
answered by alpha 7
·
0⤊
0⤋
x² - 4x - 12 = 0
(x - 6)(x +2) = 0
x = 6 or x = - 2
2007-02-01 11:18:13
·
answer #5
·
answered by Como 7
·
0⤊
0⤋
(x+2)(x-6)=0
2007-02-01 11:10:03
·
answer #6
·
answered by puakk 2
·
0⤊
0⤋
(x-6)(x+2)
2007-02-01 11:10:47
·
answer #7
·
answered by tarundeep300 3
·
0⤊
0⤋
x² - 4x - 12 = 0
x² + 2x - 6x - 12
x(x + 2) - 6(x + 2)
(x - 6)(x + 2)
- - - - - - - - - -s-
2007-02-01 11:25:23
·
answer #8
·
answered by SAMUEL D 7
·
0⤊
0⤋
(x+2)(x-6)=0
x=-2,6
2007-02-01 11:25:13
·
answer #9
·
answered by Dave aka Spider Monkey 7
·
0⤊
0⤋